Thin-plies in adhesively bonded carbon fiber reinforced polymers. (1st March 2020) - Kupski, Julian; Zarouchas, Dimitrios; Teixeira de Freitas, Sofia
Abstract: The aim of this study is to evaluate the enhanced off-axis properties of thin plies to improve the performance of adhesively bonded carbon fiber reinforced polymers. Single lap bonded joints with three different ply thicknesses of 200 μm, 100 μm and 50 μm were tested under quasi-static tensile loading. Acoustic Emission and Digital Image Correlation were used to monitor the damage and strain evolution of the overlap area during testing. 3D post-mortem failure analysis of the fracture surfaces were performed using a 3D profiling microscope. Experimental results show an increase of 16% in the lap shear strength and an increase of 21% in the strain energy when using the 50 μm instead of 200 μm ply thicknesses. However, Acoustic Emission measurements show that the damage initiation is postponed up to a 47% higher load when using 50 μm instead of 200 μm ply thicknesses. Moreover, the total amount of acoustic energy released from initiation up to final failure was significantly less with thin plies. A non-linear finite element analysis up to damage initiation indicates that with decreasing ply thickness, the damage onset inside the composite is postponed to higher loads and moves away from the adhesive interface towards the mid-thickness of the adherend. It is found that, decreasing the single ply thickness of laminated composite adherends in a single overlap bonded joint increases the maximum load and delays damage initiation of the joint, however the damage progression till final failure is more sudden.